The blood countess : murder, betrayal, and the making of a monster - Puhak, Shelley (Bloomsbury Publishing, 2026)
A "work of true crime and feminist history about Elizabeth Bathory, the woman alleged to be the world's most prolific female serial killer, [but who the author believes was a widow whose large landholdings and religious beliefs made her a target for ambitious men, and who was an herbalist who used plant-based medicines, rather than a murderer]"--